Evidence of hydroxyl radical created by DBD plasma in water and its application in dye wastewater remediation - Wang Ying; Wang Weiwei; Ji Yingchao; Li Hong; Wang Qiuhong (Functional Materials, 2016)
Dye wastewater remediation becomes a global concern. In this paper DBD plasma technology was used for water treatment. To find the evidence of hydroxyl radical created by DBD plasma in water, crystal violet (CV) was used as the radical indictor. The results showed that the hydroxyl radicals can survive longer in water solution than in gaseous state. Water increased the dye decoloration efficiency. Then CV and Methyl Orange (MO) solutions were chosen as dye wastewater. During plasma discharge, a large number of strong hydroxyl radicals in water attacked the dye molecules, resulting in the bleaching of the solution. The color groups of the CV and MO dye were effectively decomposed by plasma. The decoloration rate of the dye solutions was promoted with the increasing of plasma treatment time. 0.1 % CV solution needed 2 min to fade and 0.1 % MO solution needed 3 min to fade at the discharge condition of 100 W and 8 mm. The energy yields obtained in this investigation were 0.24 g/kWh for MO dye and 0.36 g/kWh for CV dye.